A cidade e a favela: o “Poço da Draga” e a requalificação urbana em Fortaleza - Sousa, Vancarder Brito (2006)
This work evaluates changes generated by socio-spatial activities that occurred within a slum area in Fortaleza, Ceara, called Comunidade do Poço da Draga (Poço da Draga Community), especially those actions resulting from a “urban renewing process” that started in 1990 due to a raising regional competition trend exploring tourism and events as seen in the metropolis. In 2001, within this “qualification process”, the State Government announced the launching of a project sponsored by Centro Multifuncional de Eventos e Feiras do Ceara-CMEFC whose facilities would be built where the afore-mentioned community is located. From the very announcement several reactions have been detected and are the main focus of this research work that aims at amplifying our understanding of the phenomenon.